Influence of sodium bicarbonate treatment on the aging resistance of natural fiber reinforced polymer composites under marine environment. (December 2019) - Fiore, V.; Sanfilippo, C.; Calabrese, L.
Abstract: Aim of the current study is to investigate how an innovative and eco-friendly chemical treatment based on sodium bicarbonate solution (10 wt%) can improve the aging resistance in marine environment of epoxy based composites, reinforced with flax and jute fibers. To this scope, treated and untreated fiber reinforced composites were manufactured through vacuum infusion technique. The resulting composites were then exposed to salt-fog spray conditions up to 60 days, according to ASTM B117 standard. The assessment of their durability was made by means of tensile, flexural quasi-static tests and Charpy impact tests. Furthermore, the water uptake evolution of each composite was monitored during the whole aging exposition. The experimental campaign evidenced that the beneficial effect of the sodium bicarbonate treatment on adhesion between flax fibers and epoxy matrix allows treated laminates to better retain their flexural properties during the salt-fog-exposition, in comparison to untreated laminates. Conversely, the proposed treatment leads to a slight worsening effect on the durability of jute fiber reinforced composites. Highlights: Effect of sodium bicarbonate treatment on aging resistance of flax and jute reinforced epoxy composites was evaluated. Treated and untreated fiber reinforced composites were manufactured through vacuum infusion. Composites were exposed to salt-fog spray up to 60 days, according to ASTM B117 standard. Quasi-static tests and Charpy impact tests were performed to assess the composites durability. Water uptake evolution of each composite was monitored during the aging exposition.